Representation of the Old Believers in Poland in ethnographic photography - Jewdokimow, Dorota (Przegla̜d religioznawczy, 2022)
The Old Believers are a religious and ethnic minority dwelling in the northeastern part of Poland. That religious group was formed as a result of the reforms within the Russian Orthodox Church, which took place in the 17th century. A large proportion of the Russian community objected to the radical changes introduced by patriarch Nikon, which gave rise to the Raskol. The authorities responded with mass repressions resulting in the migrations of Russians abroad, also to Poland. After the Second World War, the Old Believers in Poland attracted considerable interest of both journalists and academics. The post-war period saw a fair a number of publications describing the culture of the Old Ritualists that yielded a relatively comprehensive image of that community. The aim of this paper is to outline the mechanism behind the portrayal of the Old Believers through photography, which in the investigations of cultural anthropologists becomes the tool of capturing cultural reality, as well as the object of their research. Here, the analysis is concerned with the collection of ethnographic photographs by Eugeniusz Iwaniec. The author goes beyond the limitations of traditional understanding of ethnographic photography, qualified by virtue of its subject matter, extending the scope of such a notion by integrating the perspective of visual anthropology to reveal additional aspects of the analysed material, including the authors, the concept, the subject and the reception, which later become key reference points for the analysis.